2014
DOI: 10.1155/2014/178323
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Endovascular Repair of Ruptured Abdominal Aortic Aneurysm on the Gastrointestinal and Renal Function

Abstract: Introduction. Systemic effects of ruptured abdominal aortic aneurysm (rAAA) may be altered by the mode of surgery. This study aimed to determine systemic effects of endovascular aneurysm repair (EVAR) compared to open repair (OR). Patients and Methods. Consecutive patients with rAAA were repaired by OR or EVAR according to computerised tomographic (CT) findings. Renal function was monitored by estimated glomerular filtration rate (eGFR), serum urea and creatinine, and urinary albumin creatinine ratio (ACR). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Emergency EVAR also carries the risk of several complications like those encountered after OSR. Whether EVAR is superior to OSR in terms of major morbidity remains to be seen, 455 however, a recent analysis of the Vascular Quality Initiative (2003e 2013) database (514 EVAR, 651 OSR) suggested that EVAR is associated with lower in hospital morbidity than OSR. 456 Specifically, the incidence of cardiac complications (EVAR, 29% vs. OSR, 38%; p ¼ 0.001), respiratory complications (28% vs. 46%; p < 0.0001), renal insufficiency (24% vs. 38%; p < 0.0001), lower extremity ischaemia (2.7% vs. 8.1%; p < 0.0001), and bowel ischaemia (3.9% vs. 10%; p < 0.0001) were significantly lower after EVAR than after OSR.…”
Section: Recommendation 69mentioning
confidence: 99%
“…Emergency EVAR also carries the risk of several complications like those encountered after OSR. Whether EVAR is superior to OSR in terms of major morbidity remains to be seen, 455 however, a recent analysis of the Vascular Quality Initiative (2003e 2013) database (514 EVAR, 651 OSR) suggested that EVAR is associated with lower in hospital morbidity than OSR. 456 Specifically, the incidence of cardiac complications (EVAR, 29% vs. OSR, 38%; p ¼ 0.001), respiratory complications (28% vs. 46%; p < 0.0001), renal insufficiency (24% vs. 38%; p < 0.0001), lower extremity ischaemia (2.7% vs. 8.1%; p < 0.0001), and bowel ischaemia (3.9% vs. 10%; p < 0.0001) were significantly lower after EVAR than after OSR.…”
Section: Recommendation 69mentioning
confidence: 99%
“…U pacientů indikovaných k léčbě AAA je vždy riziko zhoršení renálních funkcí v souvislosti se zákrokem. Toto riziko je vlastní oběma metodám léčby -chirurgické i endovaskulární [10,11]. Řada studií srovnávala výsledky obou metod se zaměřením na pooperační zhoršení renálních funkcí.…”
Section: Diskuseunclassified
“…Indeed evidence is emerging that the inflammatory response to RAAA repair and the associated organ dysfunction is attenuated by eEVAR compared with open repair. 31 32 …”
Section: Introductionmentioning
confidence: 99%